2022
DOI: 10.3389/fimmu.2022.865593
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Resident Foxp3+ Regulatory T Cells: Sentinels and Saboteurs in Health and Disease

Abstract: Foxp3+ regulatory T (Treg) cells are a CD4 T cell subset with unique immune regulatory function that are indispensable in immunity and tolerance. Their indisputable importance has been investigated in numerous disease settings and experimental models. Despite the extensive efforts in determining the cellular and molecular mechanisms operating their functions, our understanding their biology especially in vivo remains limited. There is emerging evidence that Treg cells resident in the non-lymphoid tissues play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 198 publications
(259 reference statements)
0
14
0
Order By: Relevance
“…Recipient Tregs show increased persistence after conditioning regimens due to their increased radio-resistance when compared to Conventional T cells (Tcons). Such radio-resistance correlated with higher Bcl2 expression levels in rTregs and leads to the persistence of tissue resident recipient T cells, including Foxp3+ Tregs, after HSCT ( 7 ). Some studies have shown that after HSCT, recipient Tregs are able to expand in an IL2 dependent manner, providing some protection against GvHD.…”
Section: Rtregs Manipulation As a Potential Approach For Successful H...mentioning
confidence: 99%
“…Recipient Tregs show increased persistence after conditioning regimens due to their increased radio-resistance when compared to Conventional T cells (Tcons). Such radio-resistance correlated with higher Bcl2 expression levels in rTregs and leads to the persistence of tissue resident recipient T cells, including Foxp3+ Tregs, after HSCT ( 7 ). Some studies have shown that after HSCT, recipient Tregs are able to expand in an IL2 dependent manner, providing some protection against GvHD.…”
Section: Rtregs Manipulation As a Potential Approach For Successful H...mentioning
confidence: 99%
“…These ST2-positive tissues Treg express tissue-regenerative factors such as Amphiregulin (Areg) alongside T helper 2 (Th2)-associated factors, including high levels of transcription factor Gata3 [ 21 ]. Tissue homeostasis and specific functions of ST2-positive Treg cells have been characterized in different non-lymphoid tissues like visceral adipose tissue (VAT), muscle, colon, and skin [ 22 , 23 , 24 , 25 ]. All these Treg subtypes, including both FOXP3-dependent and -independent developed Treg populations, are thought to be essential for maintaining tissue homeostasis and immune tolerance [ 12 , 23 ].…”
Section: Treg Subsets and Functions Within The Immune Systemmentioning
confidence: 99%
“…FOXP3 + Tregs not only play essential role in the maintenance of immune homeostasis, but also play an indispensable role in regulating tissue homeostasis, inflammation and repair when resident in non-lymphoid tissues (51). The tissue resident Tregs own diverse functions, appeared in multiple sites including adipose tissue, cardiac muscle, skeletal muscle, lung, liver, central nervous system, skin and other tissues (51,52).…”
Section: Function and Mechanism Of Treg: More Than Immunosuppressionmentioning
confidence: 99%
“…FOXP3 + Tregs not only play essential role in the maintenance of immune homeostasis, but also play an indispensable role in regulating tissue homeostasis, inflammation and repair when resident in non-lymphoid tissues (51). The tissue resident Tregs own diverse functions, appeared in multiple sites including adipose tissue, cardiac muscle, skeletal muscle, lung, liver, central nervous system, skin and other tissues (51,52). Recently we have revealed that insulin signaling induced the transition of visceral adipose tissue Tregs from CD73 hi ST2 lo subset into a CD73 lo ST2 hi subset through the HIF-1a/Med23-PPARg axis and thus influenced beige fat production (53).…”
Section: Function and Mechanism Of Treg: More Than Immunosuppressionmentioning
confidence: 99%